2017
DOI: 10.13164/mendel.2017.1.065
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Algorithm for Independent Job Scheduling in Grid Computing

Abstract: Grid computing refers to the infrastructure which connects geographically distributed computers ownedby various organizations allowing their resources, such as computational power and storage capabilities, to beshared, selected, and aggregated. Job scheduling is the problem of mapping a set of jobs to a set of resources.It is considered one of the main steps to e ciently utilise the maximum capabilities of grid computing systems.The problem under question has been highlighted as an NP-complete problem and henc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…The two proposed hybrid methods,ACO-VNS and GA-VNS, were compared against selected algorithms from the literature. In particular, the following algorithms were selected for comparison: min-min algorithm [9], Genetic Algorithm (GA) [17], Simulated Annealing (SA) [17], Particle Swarm Optimisation (PSO) [17], Differential Evolution algorithm (DE) [18], Two-Phase Variable Neighbourhood Search (TPVNS) [16] and Genetic Algorithm (MGA) [34]. All the competing algorithms were implemented sequentially.…”
Section: Results For Instances From Liu Et Al [17]mentioning
confidence: 99%
See 3 more Smart Citations
“…The two proposed hybrid methods,ACO-VNS and GA-VNS, were compared against selected algorithms from the literature. In particular, the following algorithms were selected for comparison: min-min algorithm [9], Genetic Algorithm (GA) [17], Simulated Annealing (SA) [17], Particle Swarm Optimisation (PSO) [17], Differential Evolution algorithm (DE) [18], Two-Phase Variable Neighbourhood Search (TPVNS) [16] and Genetic Algorithm (MGA) [34]. All the competing algorithms were implemented sequentially.…”
Section: Results For Instances From Liu Et Al [17]mentioning
confidence: 99%
“…Several selection techniques are available in the literature. In this study, the N-Tournament method suggested in [10] [34] has been used with N=4. In tournament selection, several tournaments are run among a few individuals which have been selected randomly from the population.…”
Section: The Selection Operatormentioning
confidence: 99%
See 2 more Smart Citations
“…Authors in [24] proposed a novel genetic algorithm (Im-GA) based independent task scheduling technique to optimize four conflicting objectives, makespan, load balancing, resource utilization, and speed up ratio using a novel mutation technique. Authors in [25] also proposed a GA based scheduling algorithm for scheduling Bag-of-tasks in computational grids using modified mutation strategy to improve the makespan. The proposed GA obtained best makespan over many sequential task scheduling methods, Authors in [26] proposed six multiobjective genetic algorithms using single and multiple population schemes for solving the scheduling problem of batch of independent tasks in Computational Grid (CG).…”
Section: B Scheduling On Independent Sequential Jobsmentioning
confidence: 99%